New Mediterranean Biodiversity Records (July 2016) - T. DAILIANIS; O. AKYOL; N. BABALI; M. BARICHE; F. CROCETTA; V. GEROVASILEIOU; R. CHANEM; M. GÖKOĞLU; T. HASIOTIS; A. IZQUIERDO-MUÑOZ; D. JULIAN; S. KATSANEVAKIS; et al. (Mediterranean Marine Science, 2016)
This contribution forms part of a series of collective articles published regularly in Mediterranean Marine Science that report on new biodiversity records from the Mediterranean basin. The current article presents 51 geographically distinct records for 21 taxa belonging to 6 Phyla, extending from the western Mediterranean to the Levantine. The new records, per country, are as follows: Spain: the cryptogenic calcareous sponge Paraleucilla magna is reported from a new location in the Alicante region. Algeria: the rare Atlanto-Mediterranean bivalve Cardium indicum is reported from Annaba. Tunisia: new distribution records for the Indo-Pacific lionfish Pterois miles from Zembra Island and Cape Bon. Italy: the ark clam Anadara transversa is reported from mussel cultures in the Gulf of Naples, while the amphipod Caprella scaura and the isopods Paracerceis sculpta and Paranthura japonica are reported as associated to the –also allochthonous–bryozoan Amathia verticillata in the Adriatic Sea; in the latter region, the cosmopolitan Atlantic tripletail Lobotes surinamensisis also reported, a rare finding for the Mediterranean. Slovenia: a new record of the non-indigenous nudibranch Polycera hedgpethi in the Adriatic. Greece: several new reports of the introduced scleractinian Oculina patagonica, the fangtooth moray Enchelycore anatina, the blunthead puffer Sphoeroides pachygaster (all Atlantic), and the lionfish Pterois miles (Indo-Pacific) suggest their ongoing establishment in the Aegean Sea; the deepest bathymetric record of the invasive alga Caulerpa cylindracea in the Mediterranean Sea is also registered in the Kyklades, at depths exceeding 70 m. Turkey: new distribution records for two non indigenous crustaceans, the blue crab Callinectes sapidus (Atlantic origin) and the moon crab Matuta victor (Indo-Pacific origin) from the Bay of Izmir and Antalya, respectively; in the latter region, the Red Sea goatfish Parupeneus forsskali, is also reported. Lebanon: an array of records of 5 alien and one native Mediterranean species is reported by citizen-scientists; the Pacific jellyfish Phyllorhiza punctata and the Indo-Pacific teleosteans Tylerius spinosissimus, Ostracion cubicus, and Lutjanus argentimaculatus are reported from the Lebanese coast, the latter notably being the second record for the species in the Mediterranean Sea since 1977; the native sand snake-eel Ophisurus serpens, rare in the eastern Mediterranean, is reported for the first time from Lebanon, this being its easternmost distribution range; finally, a substantial number of sightings of the lionfish Pterois miles further confirm the current establishment of this lessepsian species in the Levantine.